Ocular pathology in aquarium fish with a focus on the Syngnathidae and Apogonidae families. (January 2023) - Kumaratunga, Vim; Adams, Vicki J; Donaldson, David; Pont, Roser T; Stidworthy, Mark F
ABSTRACT: This study catalogued ocular pathology in fish histopathology submissions to a specialist diagnostic service and investigated associations with species and systemic disease, with a focus on species of conservation interest. Cross-tabulations and Fisher's exact tests were used to identify associations among the variables and results are reported as prevalence ratios (PRs) with 95% confidence intervals (CI). Of 12, 488 reports reviewed, ocular histology examination was available for 4, 572 submissions, in which histopathological ocular lesions were identified in 18% (813/4572). Most diagnoses (701/813; 87%) were in marine fish. Inflammatory conditions were most common (608/813; 75%), with identification of a bacterial aetiology in 42% (255/608) and a parasitic aetiology in 30% (183/608). Most bacterial infections were due to mycobacteriosis (153/255; 60%) and most parasitic infections were due to scuticociliatosis (114/184; 62%). The Syngnathidae, Centriscidae and Cichlidae families were each more likely than all other families combined to be diagnosed with ocular manifestations of mycobacteriosis (PRs = 2.6, 4.4 and 2.9, respectively, P  <0.0001 for each). The Syngnathidae were also more likely to be diagnosed with ocular scuticociliatosis (PR = 1.9, P  <0.0001). Fifty-four percent (39/72) of ocular mycobacteriosis and 38% (9/24) of gas bubble disease cases affected threatened or near threatened Syngnathidae species. The Apogonidae were more likely than any other family to have ocular iridovirus (PR = 10.3, 95% CI = 5.5–19.4, P  <0.0001) and neoplasia (PR = 8.2, 95% CI = 4.2–16.3, P  <0.0001). The endangered Banggai cardinalfish ( Pterapogon kauderni ) accounted for 13/15 ocular iridovirus and 16/18 mycobacteriosis cases in this family. All cases of neoplasia in the Apogonidae occurred in pajama cardinalfish ( Sphaeramia nematoptera ). These results should inform clinical diagnosis of ocular disease in aquarium fish and influence training for aquarists, highlighting ocular pathology as a potential early warning of systemic disease. The findings also have direct/indirect consequences for the welfare and conservation of some of these popular flagship fish species. Graphical abstract: Eye lesions such as exophthalmos are common and clinically obvious in fish and this study seeks to highlight the wide range of primary ocular disorders and underlying systemic disease processes identified in a large cohort of aquarium fish through the use of routine histopathological surveillance. Image 1